FIOH-sponsored newsletter misrepresents asbestos hazards in Zimbabwe - (:unkn) unknown (My University, 2006)
The Finnish Institute of Occupational Health (FIOH) has received support from the World Health Organization (WHO) and the International Labor Office (ILO) to publish the African Newsletter on Occupational Health and Safety. The African Newsletter on Occupational Health and Safety should not be a medium for industry propaganda, or the source of misinformation among the workers of Africa. Instead, FIOH should provide the same level of scientific information in Africa that it does in Finland and other developed countries.
Keywords: African Research